Lymphocyte phenotyping in untreated children patients with chronic allergic asthma (Baghdad Science Journal, 2025)
This study aimed to isolate and phenotype lymphocytes in untreated children patients with chronic allergic asthma. To reach such aim the study involved (25) patients from children (17 male and 9 female) whom their ages where between (3-10) years, in addition to (15) apparently healthy children (9 male and 6 female) in the same ages involved as control group. The data demonstrated that there was a significant increase in the mean percentages of T-lymphocytes (CD3+ cells) in the peripheral blood of patients (66.75±0.29)**, in comparison with control group (43.58±0.19), a significant increase in the mean percentages of T-helper lymphocytes (CD4+ cells) in the peripheral blood of patients (51.14±0.55), in comparison with control group (39.17±0.23) and the mean percentages of B-lymphocytes (CD20+ cells) was also increased significantly in the peripheral blood of patients (29.63±0.20) when it compared with the mean percentages of the same cells in control group (18.60±0.80). Besides a significant decrease in the mean percentages of T-suppressor lymphocytes (CD8+ cells) in the peripheral blood of patients (11.31±0.05), in comparison with control group (16.42±0.15). Finally the results of this study showed a significant increase in the mean percentages of the ratio of (CD4+ cells/CD8+ cells) in the peripheral blood of patients (55.34±0.41), in comparison with control group (31.25±0.09).